PENGARUH MUTU DAN PROSEDUR PELAYANAN BANTUAN LANGSUNG TUNAI TERHADAP KEPUASAN LANSIA KECAMATAN MENGGALA - Ivo Miduwanto; Agus Wahyudi; Elip Heldan (Universitas Bandar Lampung (UBL), 2022)
The impact of service standards and operating practices on elderly BLT recipients' satisfaction (the study was conducted on BLT Recipient Elderly in Menggala District, Tulang Bawang Regency). Every public service organization, in theory, places a strong emphasis on the satisfaction of the community's and consumers' own expectations for service quality and service procedures. The primary focus of this study is on service quality and operational procedures in an effort to determine how they affect community happiness, which in this case refers to the elderly getting BLT. Data gathering methods for this study's quantitative approach include surveys, written materials, and questionnaires. Tulang Bawang Regency's Menggala District served as the site of the research. A Likert scale is used in this investigation. In this study, a sample of 72 samples was produced from a population of 253 elderly BLT recipients by utilizing the Slovin formula to calculate the number of samples with a tolerance value of 10%. The Community Satisfaction Index (IKM) for service quality was 4.14 with a conversion of 82.8 in the